1996
DOI: 10.1111/j.1469-8137.1996.tb01853.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐scale patterns of modern pollen deposition within three alpine plant communities*

Abstract: SUMMARYFew studies have examined patterns of pollen deposition or the relationship between vegetation and pollen assemblages at the small scale. This paper examines the representation of both individual taxa and whole plant communities in modern pollen spectra. Micro-scale variations in modern pollen deposition were studied in three alpine plant communities on Storbreen glacier foreland, southern Norway: a pioneer community; a 5a/ij:-shrub community; and an ericaceous heath community. The relationships between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…For example, the best modern analogue of a fossil sample might be a single moss sample, since fossil samples from a peat core are also from a single location. However, previous studies such as Pardoe (1996) have shown a high degree of local variability in pollen assemblages collected in moss samples over a small area. It might, therefore, be preferable to combine several subsamples since this will be more representative of the local vegetation.…”
Section: Methods Of Collecting Moss Samplesmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, the best modern analogue of a fossil sample might be a single moss sample, since fossil samples from a peat core are also from a single location. However, previous studies such as Pardoe (1996) have shown a high degree of local variability in pollen assemblages collected in moss samples over a small area. It might, therefore, be preferable to combine several subsamples since this will be more representative of the local vegetation.…”
Section: Methods Of Collecting Moss Samplesmentioning
confidence: 89%
“…The collection of surface pollen in moss samples for calibration datasets or modern analogues is now a wellestablished technique (see for example Hicks 1977;Hjelle 1998;Caseldine 1989;Pardoe 1996Pardoe , 2001Pardoe , 2006Tonkov et al 2001). Moss samples are also used extensively in studies of pollen productivity and dispersal (Räsänen et al 2004), such as those published by Broström et al (2004Broström et al ( , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…These occurrences are easily detected in the scatter plots, and may argue against the common use of the amalgamation of pollen samples in surface-sample investigations (e.g. Adam and Mehringer 1975;Berglund et al 1986;Pardoe 1996). Combinations of pollen samples will result in a lower mean value, but nevertheless a value higher than that obtained by natural dispersal (cf.…”
Section: Discussionmentioning
confidence: 94%
“…Micro-scale variation in pollen assemblages has been little studied though it may be significant (Pardoe, 1996), especially where there is micro-topographical variation within the sampling site (Kitcher, 2014). Earlier studies have recommended an amalgam of mosses from multiple points within a small area (Broström et al, 2004;Räsänen et al, 2004; et al, 2008), and although this has its own limitations (for example, in areas where mosses are sparse such as meadows multiple mosses will not occur in close proximity; ensuring sampling is unbiased both in the field and when subsampling for extraction requires extra time and care; a single outlying assemblage will raise the average of the taxa concerned in the mixed sample, and is less likely to be detected) it may give more representative results.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Taking multiple samples within a small area of known radius (e.g. Broström et al, 2004;Mazier et al, 2008) to mitigate against micro-scale variations in pollen influx has been shown to be effective for both moss polsters (Pardoe, 1996) and surface soil samples (Adam and Mehringer, 1975).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%